The long-term outcomes after smiley face rod surgery in young lumbar spondylolysis patients - Qiang Zhang; Zhe Chen; Yazhou Lin; Jianru Qiu; Xinkai Zhang; Peng Cao; Wenjian Wu; Yu Liang (Scientific Reports)
Abstract To investigate the long-term outcomes of young spondylolysis patients treated with smiley face rod surgery. The study is a retrospective analysis of the clinical data of 45 young lumbar spondylolysis patients from 2008 to 2024. All patients underwent smiley face rod surgery and the follow-up period ranged from 3 months to 17 years. The clinical outcomes (VAS score, ODI index, and Odom score) and radiological evaluations were compared before/after surgery and at the final follow-up. All the participations reported satisfactory short-term outcomes after smiley face rod surgery, with VAS scale and ODI index improved significantly 3 months after surgery. The VAS scale and ODI index both maintained good enough until final follow-up (mean 11.2 years). The successful union rate was only 57.5% at 12 months after surgery and 58.6% at final follow-up, as shown in 3D-CT scan. And the VAS and ODI scales had no statistical difference between the healed and unhealed patients. The smiley face rod technique demonstrated long-term satisfactory outcomes for treating young spondylolysis. Though the healing rate was only 57.5–58.6%, all patients reported excellent clinic outcomes and the healing status had no impact on clinic outcomes.